Strategi Pengembangan Usahatani Nanas Pada Kelompok Tani Sinjay Di Desa Astomulyo Kecamatan Punggur, Lampung Tengah - M. Lathiifu Razzaq; Supriyadi Supriyadi; Ainul Mardliyah; Fikri Syahputra (JURNAL WACANA PERTANIAN, 2022)
This study aims to determine the appropriate development strategy in an effort to increase pineapple farming in the Sinjay Farmer Group in Astomulyo Village Punggur District Central Lampung Regency. This research was conducted at the Sinjay Farmer's Group in Astomulyo Village Punggur District Central Lampung Regency. The number of samples in this study were 55 pineapple farmers and all of them were used as samples. The sampling method uses the saturated side (census) for all farmers in the population. The analytical method used in this research is SWOT analysis to find out the existing internal and external factors. The results of this study indicate that based on the results of the analysis on the SWOT matrix, the recommendation that must be given is the "Progressive" strategy. Strategies that can be applied are increasing pineapple cultivation skills by utilizing the cooperation of farmer group members to produce higher quality products, optimizing pineapple cultivation management by adopting modern agricultural technology so as to increase the productivity of pineapples produced, and optimizing land resources owned in producing quality products. through increasing soil fertility with the use of organic fertilizers.